Penyuluhan Kesehatan Pencegahan Infeksi Nosokomial di Rumah Sakit Undata Provinsi Sulawesi Tengah - Hidayat, Elin; Fristalia, Mikaela Delpin; Huda, Izul; Akhir, M. Hian; W, Wahyuni; M, Munifa; Pratiwi, Nabila (Nanggroe: Jurnal Pengabdian Cendikia, 2024)
Hospital-acquired infections, which are infections acquired by patients while in healthcare facilities, present a serious challenge in healthcare delivery with widespread impacts on care quality and costs. These infections not only worsen the patients' conditions but also place additional burdens on the healthcare system as a whole. According to existing data, the prevalence of hospital-acquired infections in Indonesia ranges from 10% to 15%, highlighting the importance of prevention efforts. This community service report details the implementation of health education at Undata Hospital in Central Sulawesi Province, aimed at increasing patients' and families' knowledge about preventing hospital-acquired infections. The implementation methods involved thorough planning, development of educational materials, and practical training on infection prevention techniques. The results of the education showed a significant improvement in participants' knowledge and skills, with understanding increasing from 45% to 85% and prevention compliance reaching 80%. However, challenges such as resource limitations and varying levels of adherence persist. Therefore, regular education, facility improvements, and periodic evaluations are recommended to optimize the prevention of hospital-acquired infections. This study underscores the need for a multifaceted and comprehensive approach to reduce the incidence of hospital-acquired infections and enhance patient safety in healthcare facilities